Lightweight amorphous silicon photovoltaic modules on flexible plastic substrate - Vygranenko, Yuri (2015)
Solar cells on lightweight and flexible substrates have advantages over glass-or wafer-based photovoltaic devices in both terrestrial and space applications. Here, we report on development of amorphous silicon thin film photovoltaic modules fabricated at maximum deposition temperature of 150 degrees C on 100 mu m thick polyethylene-naphtalate plastic films. Each module of 10 cm x 10 cm area consists of 72 a-Si:H n-i-p rectangular structures with transparent conducting oxide top electrodes with Al fingers and metal back electrodes deposited through the shadow masks. Individual structures are connected in series forming eight rows with connection ports provided for external blocking diodes. The design optimization and device performance analysis are performed using a developed SPICE model.